การบริหารทรัพยากรมนุษย์ขององค์การและแรงจูงใจที่ก่อให้เกิดความเครียด ในการปฏิบัติงาน กรณีศึกษาพนักงานบริษัทเอกชนแห่งหนึ่ง - แก้วพลายงาม ภัทรารัช; ธรรมจินดา วสุ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to: 1. study the motivations causing work stress among employees of a private company 2. compare the motivations causing work stress categorized by personal factors and 3. study the relationship between motivation and stress among employees of a private company. The sample consisted of employees of a private company. The research instrument was a questionnaire. Descriptive statistics, including percentages, means, and standard deviations, were used for data analysis. Inferential statistics, including t-test and One-way ANOVA, were employed. The results showed that the majority of personal factors differed, with differences in gender, age, education level, length of service, and average monthly income. Overall, the motivations causing stress were at a high level, with the highest mean score being related to job characteristics, followed by relationships and career advancement, respectively. Hypothesis testing revealed that different personal factors did not significantly affect motivations causing stress. Furthermore, a statistically significant positive correlation was found between work motivation and work stress.